Hydrocarbon anomalies using airborne gamma radiation over the unconventional petroleum system of the South Portuguese Zone, Portugal. (December 2020) - Barberes, Gabriel A.; Barata, Maria Teresa; Pena dos Reis, Rui; Spigolon, André L.D.
Abstract: The use of airborne gamma radiation in hydrocarbon exploration is widely known to define possible areas of microseepage. At this paper, the radiometric survey was applied to identify hydrocarbon anomalies over the South Portuguese Zone (SPZ) unconventional petroleum system. Spectral gamma-ray data were processed to thorium normalization method. Obtained results show positive anomalies mainly on the southwest sector of the SPZ, corroborating the data obtained through fluid geochemical analysis, revealing other several surface sweet spots for hydrocarbons emanations. Highlights: Surface geochemical prospecting for hydrocarbon exploration. Airborne gamma radiation applied to unconventional petroleum system characterization. Hydrocarbon microseeps detection over the South Portuguese Zone.